Multidecadal Recession of Grinnell and Terra Nivea Ice Caps, Baffin Island, Canada - Way, Robert G. (ARCTIC, 2015)
Multi-temporal satellite imagery and historical aerial photography reveal that two southern Arctic ice caps on Baffin Island have shrunk considerably over the past several decades. Satellite remote sensing shows that over the past three decades, the Grinnell and Terra Nivea ice caps, the southernmost ice caps in the eastern Canadian Arctic, have decreased in area by 18% and 22% respectively, which corresponds to a total area decline of 68 km2 since the inventory done in the late 1950s. Cumulative ice loss since the mid-1970s has occurred at a rate of −1.69 km2/yr. The Grinnell ice cap has declined in area by −0.57 km2/yr, while the larger Terra Nivea ice cap has lost ice at a rate of −1.1 km2/yr. Interior thinning has led to the exposure of nunataks far from ice margins, and outlet glaciers have retreated substantial distances up-valley. The rapid reduction in ice area is linked directly to increasing summer air temperatures and suggests that these ice caps are in disequilibrium with current climate. Projections suggest that if the observed ice decline continues to AD 2100, the total area covered by ice at present will be reduced by more than 57%. L’imagerie satellitaire multitemporelle et la photographie aérienne historique révèlent que deux calottes glaciaires du sud de l’Arctique, dans l’île de Baffin, ont rétréci considérablement au cours des dernières décennies. La télédétection par satellite montre qu’au cours des trois dernières décennies, l’étendue des calottes glaciaires Grinnell et Terra Nivea, soit les calottes glaciaires les plus au sud de l’Arctique canadien de l’est, a diminué dans une mesure de 18 % et de 22 % respectivement, ce qui correspond à un déclin total de l’étendue de 68 km2 depuis que l’inventaire a été dressé vers la fin des années 1950. Depuis le milieu des années 1970, la perte cumulative de glace s’est produite au taux de −1,69 km2/an. L’étendue de la calotte glaciaire Grinnell a diminué de −0,57 km2/an, tandis que la calotte glaciaire Terra Nivea, dont l’étendue est plus grande, a ...